Disiplin Kerja Meningkatkan Kinerja Karyawan Melalui Kepuasan Kerja - Taufan, Sonny; Rachmawati, Pratitis Tiarra (Universitas Muhammadiyah Metro, 2024)
The current industrial development is rapidly progressing from year to year, driving all industrial companies to enhance their business operations. The purpose of this research is to analyze how work discipline improves employee performance through job satisfaction. This study employs a quantitative associative approach using a questionnaire as the data collection method. The sampling technique utilized is purposive sampling, targeting 43 sales force respondents who have been working for more than a year at PT Srikandi Diamond Motors Cakung. Data analysis is conducted using path analysis with the assistance of SPSS as the data processing application. The research findings indicate that: 1) Work discipline variables directly have a significant influence on increasing job satisfaction, 2) Work discipline directly has a significant influence on improving employee performance, 3) Job satisfaction directly has a significant influence on enhancing employee performance, 4) Work discipline indirectly and significantly improves employee performance through job satisfaction. The recommendation from this study regarding sales job satisfaction is to not require sales staff to attend work if there is no provision of basic salary, with the condition of meeting sales targets.